2020
DOI: 10.1155/2020/5348730
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries Prediction Based on a Survey of the Oral Health Epidemiology among the Geriatric Residents of Liaoning, China

Abstract: Background. Dental caries is one of the most common chronic diseases observed in elderly patients. The development of preventive strategies for dental caries in elderly individuals is vital. Objective. The objective of the present study was to construct a generalized regression neural network (GRNN) prediction model for the risk assessment of dental caries among the geriatric residents of Liaoning, China. Methods. A stratified equal-capacity random sampling method was used to randomly select 1144 elderly (65-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Therefore, we speculate that the GRNN model has better performance than the LR model for the prognostic prediction for acute stroke. Similar results have been reported by Liu et al [ 14 ], who reported that GRNN models may have better predictive ability than traditional multivariate LR models for dental caries based on the outcomes of an oral health epidemiology survey. Currently, GRNN models have shown use in predicting obstructive sleep apnea [ 27 ], quantitative structure–pharmacokinetic relationship properties of chemical agents [ 28 ], and so on.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore, we speculate that the GRNN model has better performance than the LR model for the prognostic prediction for acute stroke. Similar results have been reported by Liu et al [ 14 ], who reported that GRNN models may have better predictive ability than traditional multivariate LR models for dental caries based on the outcomes of an oral health epidemiology survey. Currently, GRNN models have shown use in predicting obstructive sleep apnea [ 27 ], quantitative structure–pharmacokinetic relationship properties of chemical agents [ 28 ], and so on.…”
Section: Discussionsupporting
confidence: 88%
“…(3) GRNN is similar in principle to neurons of the human brain; it does not have difficulties related to the use of mathematics, and it is likely to make accurate predictions [ 32 ]. However, GRNN is considered a “black box”, which makes it difficult to determine its processes and how it arrives at a prediction or explain the disease-related variables in the predictive model [ 14 ]. LR, which is a commonly used medical statistical tool, also has its irreplaceable advantages, especially in the interpretability and simplicity of finding independent parameters associated with the prognosis of stroke patients [ 8 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-carious teeth: complete teeth without fillings and without filling treatment. Caries: sulcus or smooth surface of the tooth with a softened lesion at the base, and potential damage to the enamel or softening of the sulcus wall ( Liu et al., 2020 ). The dental examination included number of permanent sound teeth, number of missing teeth from oral disease, number of decayed, missing, filled teeth (DMFT), and Number of decayed, missing, filled surfaces (DMFS).…”
Section: Methodsmentioning
confidence: 99%
“…Out of the algorithms used, SVM generated the highest performance during evaluation. Liu, L. et al [ 13 ] constructed a generalized regression neural network (GRNN) model to predict caries among residents of Liaoning, China. Using regression on some highly correlated data tends to cause spurious results and overfitting [ 14 ].…”
Section: Related Workmentioning
confidence: 99%